(untitled) (Web of Teachers: Inderscience Research, 2023)
In the article, the psycholinguistic significance of the development of the written speech of students of general secondary schools in the mother tongue in increasing the competence of written speech in English is justified. Clarifying the psycholinguistic factors of improving written speech in a foreign language based on the Uzbek national mentality was one of the important tasks of our research. In particular, the use of interactive methods based on the socio-cultural theory of language acquisition for the development of writing skills in the native language serves as an important basis for improving written speech in a foreign language.